2021
DOI: 10.1002/pds.5311
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of more than one billion outpatient prescriptions and eight‐year trend showing a remarkable reduction in antibiotic prescription in Turkey: A success model of governmental interventions at national level

Abstract: Purpose To present the antibiotic prescription trend between 2011–2018 at primary healthcare in Turkey in order to evaluate the effects of interventions at national level for providing rational prescription of antibiotics. Methods Electronic prescription data of the family physicians collected from January 1, 2011 to December 31, 2018 in 81 provinces of Turkey were recorded through the Prescription Information System and screened for the antimicrobial drugs. The interventions to promote rational antibiotic use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…Although this gap between the two groups has been increased disadvantageously for poor prescribers in some indicators, it is understood that even the physicians who have relatively good performance are not satisfactorily rational in compliance to the guidelines and current pharmacotherapy competencies. These findings reveal the necessity of the RUM improvement attempts in accordance with the current national action plan on RUM, which was recently reported to yield successful outcomes in terms of substantial reduction of antibiotic use in primary care (Aksoy et al, 2021). Refinement and/or adaptations of such interventions, especially for the most common indications with a prioritization of poorly performing physicians, could help to further improve RUM in primary care.…”
mentioning
confidence: 57%
“…Although this gap between the two groups has been increased disadvantageously for poor prescribers in some indicators, it is understood that even the physicians who have relatively good performance are not satisfactorily rational in compliance to the guidelines and current pharmacotherapy competencies. These findings reveal the necessity of the RUM improvement attempts in accordance with the current national action plan on RUM, which was recently reported to yield successful outcomes in terms of substantial reduction of antibiotic use in primary care (Aksoy et al, 2021). Refinement and/or adaptations of such interventions, especially for the most common indications with a prioritization of poorly performing physicians, could help to further improve RUM in primary care.…”
mentioning
confidence: 57%
“…However, this high percentage of patients prescribed OCS burst treatment may also reflect the fact that physicians often prescribe OCS as rescue medication in the event of worsening asthma symptoms or as part of a written asthma action plan. Furthermore, despite the introduction of two main antimicrobial stewardship programmes in Turkey [ 52 ], and a significant reduction in overall antibiotic prescriptions between 2011−2018 following governmental interventions at a national level [ 53 ], 20.5% of patients were prescribed antibiotics for asthma, indicating a lack of familiarity with asthma guidelines that do not support the routine use of antibiotics unless there is strong evidence of a lung infection [ 45 ]. Indeed, results from a Cochrane Database Systematic Review found limited evidence that antibiotics administered at the time of an asthma exacerbation may improve symptoms and peak expiratory flow rate at follow-up compared with standard care or placebo [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self-medication with antibiotics without prescription is an alarming problem, especially in low-and middle-income countries [30], but also in some Southern European countries [6][7][8][9]. While governmental interventions, such as the "Rational Drug Use National Action Plan" by the Turkish government [12], play the most crucial role in regulating and monitoring antibiotic prescription practices and availability [10], targeting self-medication among community members via policy interventions is much more chal-lenging. Self-medication with antibiotics by using leftover antibiotics, antibiotics acquired without prescription from the pharmacy, or antibiotics obtained from a friend or family member is mostly a hidden behavioural problem reflecting people's lack of knowledge, misbeliefs, and overly positive attitude to antibiotics as a "cure for everything".…”
Section: Discussionmentioning
confidence: 99%
“…In addition to an antimicrobial stewardship programme targeting hospital antibiotic use, the Turkish Ministry of Health launched a second programme (National Action Plan for Rational Drug Use 2014-2017) for curbing antimicrobial prescriptions in primary care [31]. Recent evaluations of the programme show that antibiotic prescriptions declined from 34.94% of all prescriptions in 2011 to 24.55% in 2018 [10,31]. In the present survey, however, 34.2% of respondents said that they had obtained antibiotics without a valid prescription, either from a physical or internet pharmacy or from a friend or relative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation